Exploring Green Creativity: The Effects of Green Transformational Leadership, Green Innovation Climate, and Green Autonomy - Maitlo, Qamaruddin; Wang, Xiuting; Jingdong, Yan; Lashari, Ishfaque Ahmed; Faraz, Naveed Ahmad; Hajaro, Nazim Hussain (Frontiers in Psychology, 2022)
None of the studies published in the extant literature has discussed the role of green innovation climate and green autonomy concerning green creativity and this study aims to offer these two novel constructs. By introducing the componential theory of creativity, this study explores green transformational leadership (GTL), green innovation climate, and green autonomy as antecedents of green creativity. The authors employed structural equation modeling (SEM) to analyze survey-based data collected from automotive firms in China. Data were collected from employee-supervisor working in the automotive industry located in Liaoning province, China. The findings reveal that GTL directly and indirectly via green innovation climate partially mediates the green creativity of employees in China. Moreover, green autonomy moderates the relationship between green innovation climate and green creativity. This pivotal contribution suggests that automotive business enterprises should develop GTL to nurture a green innovation climate and offer green autonomy for the green creativity of employees. The above antecedents of green creativity may enable business firms to gain a competitive advantage by innovating green products and practices.